Effectiveness of a psychoeducation group intervention conducted by primary healthcare nurses in patients with depression and physical comorbidity: study protocol for a randomized, controlled trial - Rocío Casañas; Jaume Martín Royo; Maria Isabel Fernandez-; Antonia Raya Tena; Jacobo Mendioroz; Glòria Sauch Valmaña; Roser Masa-Font; Marc Casajuana-Closas; Eva María Fernandez Linares; Cèlia Cols-Sagarra; Susana Gonzalez Tejón; Quintí Foguet-Boreu; et al. (BMC, 2019)
Abstract Background Depressive disorders are the third leading cause of consultation in primary care, mainly in patients with chronic physical illnesses. Studies have shown the effectiveness of group psychoeducation in reducing symptoms in depressive individuals. Our primary aim is to evaluate the effectiveness of an intervention based on a psychoeducational program, carried out by primary care nurses, to improve the remission/response rate of depression in patients with chronic physical illness. Secondarily, to assess the cost-effectiveness of the intervention, its impact on improving control of the physical pathology and quality of life, and intervention feasibility. Methods/design A multicenter, randomized, clinical trial, with two groups and one-year follow-up evaluation. Economic evaluation study. Subjects We will assess 504 patients (252 in each group) aged > 50 years assigned to 25 primary healthcare centers (PHC) from Catalonia (urban, semi-urban, and rural). Participants suffer from major depression (Beck depression inventory: BDI-II 13-28) and at least one of the following: type 2 diabetes mellitus, chronic obstructive pulmonary disease, asthma, and/or ischemic cardiopathy. Patients with moderate/severe suicide risk or severe mental disorders are excluded. Participants will be distributed randomly into the intervention group (IG) and control (CG). Intervention The IG will participate in the psychoeducational intervention: 12 sessions of 90 min, once a week led by two Primary Care (PC) nurses. The sessions will consist of health education regarding chronic physical illness and depressive symptoms. Main measurements Clinical remission of depression and/or response to intervention (BDI-II). Secondary measurements Improvement in control of chronic diseases (blood test and physical parameters), drug compliance (Morinsky-Green test and number of containers returned), quality of life (EQ-5D), medical service utilization (appointments and hospital admissions due to complications), and feasibility of the intervention (satisfaction and compliance). Evaluations will be blinded, and conducted at baseline, post-intervention, and 12 months follow-up. Discussion Results could be informative for efforts to prevent depression in patients with a chronic physical illness. Trial registration NCT03243799 (registration date August 9, 2017)